PRODUCTION OF MASSIVE PROFILE SLUGS AND WEAR-RESISTANT CASTINGS FOR DETAILS OF IMPORTANT ASSIGNMENT - M. A. Saikov; V. S. Grishchenko; V. M. Karpenko; M. I. Karpenko (Литьë и металлургия, 2006)
The peculiarities of production of massive wearresisting castings and profile slugs for the details of important assignment are studied. It is offered to use economdoped antifriction cast irons and the ways of casting with intensive heat-exchange for creation of such castings.